ANALYSIS OF FATAL CASES OF MECHANICAL ASPHYXIA AT BELGAUM, KARNATAKA - K S, Gurudut; Kumar S, Ajay; Gouda, Hareesh S (Journal of Forensic Medicine and Toxicology, 2012)
The present study is a retrospective evaluation of 103 deaths due to mechanical asphyxia autopsied at Dept. of Forensic Medicine and Toxicology, Belgaum Institute of Medical Sciences, Belgaum during from 01-01-2009 to 31-12-2009. Data related to age and sex of the deceased, season and manner of death were recorded with detailed autopsy examination and analyzed. Asphyxial deaths comprise 14.32% of total autopsies. Males (67.96%) outnumbered females. Most frequent method of asphyxial death was hanging (61.16%), followed by drowning (28.15%). More violent methods, such as ligature and manual strangulations, constituted 2.91% and 0.97% of all asphyxial deaths, respectively.